Pregnancy Outcomes in Women With Rheumatic Mitral Valve Disease: Results From the Registry of Pregnancy and Cardiac Disease. Issue 8 (20th February 2018) - van Hagen, Iris M.; Thorne, Sara A.; Taha, Nasser; Youssef, Ghada; Elnagar, Amro; Gabriel, Harald; ElRakshy, Yahia; Iung, Bernard; Johnson, Mark R.; Hall, Roger; Roos-Hesselink, Jolien W.
Abstract : Background: Cardiac disease is 1 of the major causes of maternal mortality. We studied pregnancy outcomes in women with rheumatic mitral valve disease. Methods: The Registry of Pregnancy and Cardiac Disease is an international prospective registry, and consecutive pregnant women with cardiac disease were included. Pregnancy outcomes in all women with rheumatic mitral valve disease and no prepregnancy valve replacement is described in the present study (n=390). A maternal cardiac event was defined as cardiac death, arrhythmia requiring treatment, heart failure, thromboembolic event, aortic dissection, endocarditis, acute coronary syndrome, and hospitalization for other cardiac reasons or cardiac intervention. Associations between patient characteristics and cardiac outcomes were checked in a 3-level model (patient–center–country). Results: Most patients came from emerging countries (75%). Mitral stenosis (MS) with or without mitral regurgitation (MR) was present in 273 women, isolated MR in 117. The degree of MS was mild in 20.9%, moderate in 39.2%, severe in 19.8%, and severity not classified in the remainder. Maternal death during pregnancy occurred in 1 patient with severe MS. Hospital admission occurred in 23.1% of the women with MS, and the main reason was heart failure (mild MS 15.8%, moderate 23.4%, severe 48.1%; P <0.001). Heart failure occurred in 23.1% of patients with moderate or severe MR. An intervention during pregnancy was performed in 16 patients, 14 had percutaneous balloon mitral commissurotomy, and 2 had surgical valve replacement (1 for MS, 1 for MR). In multivariable modeling, prepregnancy New York Heart Association class >1 was an independent predictor of maternal cardiac events. Follow-up at 6 months postpartum was available for 53%, and 3 more patients died (1 with severe MS, 1 with moderate MS, 1 with moderate to severe MR). Conclusions: Although mortality was only 1.9% during pregnancy, ≈50% of the patients with severe rheumatic MS and 23% of those with significant MR developed heart failure during pregnancy. Prepregnancy counseling and considering mitral valve interventions in selected patients are important to prevent these complications. Abstract : Supplemental Digital Content is available in the text.